2020
DOI: 10.1186/s12913-020-05223-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of shared decision-making in community rehabilitation: a focused ethnography

Abstract: Background: Shared decision-making (SDM) can advance patient satisfaction, understanding, goal fulfilment, and patient-reported outcomes. We lack clarity on whether this physician-focused literature applies to community rehabilitation, and on the integration of SDM policies in healthcare settings. We aimed to understand patient and provider perceptions of shared decision-making (SDM) in community rehabilitation, particularly the barriers and facilitators to SDM. Methods: We used a focused ethnography involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…17,19,20 Most of the studies have reported patients’ cognition of the disease and pulmonary rehabilitation, patients’ self-confidence, family, and social support as barriers to the implementation of pulmonary rehabilitation, but few have focused on the impact of the pulmonary rehabilitation decision-making process. Manhas et al 21 noted that facilitators and barriers of shared decision-making in community rehabilitation include provider characteristics, provider training, patients’ perceived assertiveness, lack of capacity, and patient-specific messaging, which are consistent with some of the findings of this study.…”
Section: Discussionsupporting
confidence: 89%
“…17,19,20 Most of the studies have reported patients’ cognition of the disease and pulmonary rehabilitation, patients’ self-confidence, family, and social support as barriers to the implementation of pulmonary rehabilitation, but few have focused on the impact of the pulmonary rehabilitation decision-making process. Manhas et al 21 noted that facilitators and barriers of shared decision-making in community rehabilitation include provider characteristics, provider training, patients’ perceived assertiveness, lack of capacity, and patient-specific messaging, which are consistent with some of the findings of this study.…”
Section: Discussionsupporting
confidence: 89%
“…The R-MoC was implemented to cultivate a patient-focused and data-informed service model. Implementing the EQ-5D-5L as a PROM in a provincial context resulted in many learnings, both with the initial pilot implementation of the 18 early adopter teams, as well as the spread and scale to 152 urban and rural sites [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this paper emphasises the survey findings, this paper is part of a broader study that included qualitative interviews, focus groups and patient-led data collection. 42 Together, this research programme followed an ethnographic methodology that underpinned its theoretical approach to data collection and analysis, which carried into this survey work equally. The surveys allowed a population-level perspective to inform the in-depth qualitative work.…”
Section: Methodsmentioning
confidence: 99%
“…This study complements another in this population that used qualitative interviews to explore SDM experiences. 42 The research team included two patient-coinvestigators who consulted on the research design, implementation and results dissemination.…”
Section: Determine Any Associations Between Sdm Experiencementioning
confidence: 99%
See 1 more Smart Citation